Sensibilidade de bipolaris sorokiniana e de drechslera tritici-repentis a fungicidas 'in vitro' - Stolte, Roseana Eda (2006)
Wheat leaf spots are usually cited as caused by the fungi Bipolaris sorokiniana, Drechslera tritici-repentis, and Stagonospora nodorum. Control by the fungicides triazoles, has been reported as inefficient in the last three growing seasons in the area of Fundação ABC, Castro, Paraná, and the hypothesis of resistance, mainly to D. tritici-repentis, was raised. Thus, the sensitivity of B. sorokiniana and of D. tritici-repentis to fungicides ‘in vitro’ was evaluated. Initially the causal agents, in samples from 2003 to 2005 growing seasons, from Paraná were identified through isolations in culture medium as well in moist chambers. Koch’s postulates were performed for each one isolate of B. sorokiniana and of D. tritici-repentis. Measurements of conidia were also done. Mycelial and conidia sensitivity (germination and germ tube length) of B. sorokiniana and mycelial of D. tritici-repentis were done ‘in vitro’ using Petri dishes with Potato Dextrose Agar as culture medium and fungicide concentrations of 0, 0,1, 1, 10 and 100 ppm added to the substratum. The following fungides were tested: azoxystrobin, cyproconazol, epoxiconazol, flutriafol, metconazol, procloraz, propiconazol, tebuconazol, and triadimenol. A completely randomized experimental design and treatment replicated three or four times were observed. The ED50, effective concentration to inhibit 50 % of fungi growth, was calculated by the equation generated by logarithmic regression analysis. Results showed that: the genus Bipolaris and Drechslera and the specie D. tritici-repentis were the main causal agents of what leaf spots; the fungus B. sorokiniana was pathogenic to oats and wheat and D. tritici-repentis just to wheat; conidia measurements of B. sorokiniana and of D. tritici-repentis were similar to the literature descriptions; there was no evident resistance of D. tritici-repentis to the fungicides; values of ED50 for B. sorokiniana were variable and showed high sensitivity up to resistance of the isolates to the fungicides azoxystrobin, flutriafol, and triadimenol.